مشكلات ومعوقات البحث الاكاديمي في الجامعة الجزائرية - صالحي, الحسين; جغل, العيد (جامعة الوادي - University of Eloued, 2021)
مما لا شك فيه أن البحث الأكاديمي أصبح ضرورة أساسية لتطوير الحياة البشرية وتحسين أداء الفرد، إذ لا تقتصر أهميته على الجامعة فحسب بل تمتد للمجتمع ككل، بيد أن هذه الأهمية تبقى مرتبطة بمدى وعي الجهة المسؤولة بأهمية البحث والمراكز البحثية، إذ يعد ذلك من المحددات الأساسية في مدى فاعلية البحوث العلمية التي تحتاج إلى عدد من المتطلبات الرئيسية في سبيل نجاحها، لاسيما أن مستوى تطور البحث العلمي في الجزائر متواضع جداً نتيجة لعوامل عديدة أهمها عدم وجود رؤية واضحة وإستراتيجية متبعة من أجل تطوير البحث العلمي ورفع نسبة الإنفاق على البحث والتطوير كنسبة من الناتج المحلي الإجمالي, إذ أضحى البحث الأكاديمي وسيلة محورية أساسية لأي أمة تريد التقدم والرقي، ولهذا فإنه من الضروري اليوم أن يعنى هذا المجال بما يجب أن يعنى به وأن يوضع في إطاره الصحيح من أجل إذلال الصعوبات وإزالة العقبات التي يعاني منها البحث الأكاديمي على مختلف مستوياته. الكلمات المفتاحية: البحث الأكاديمي, المشاكل, المعوقات. Abstract: There is no doubt that academic research has become a basic necessity for the development of human life and improving the performance of the individual, as its importance is not limited to the university, but extends to society as a whole. However, this importance remains related to the extent of awareness of the responsible body of the importance of research and research centers, as this is one of the basic determinants Regarding the effectiveness of scientific research that needs a number of basic requirements for its success, especially that the level of scientific research development in Algeria is very modest as a result of many factors, the most important of which is the lack of a clear vision and strategy followed in order to develop scientific research and raise the proportion of spending on research and development as a percentage of output Gross domestic, Academic research has become a pivotal means for any nation that wants progress and advancement, and for this it is necessary today that this field be concerned with what it should be concerned with and placed in its proper framework in order to alleviate the difficulties and remove the obstacles that academic research suffers at its various levels.
Problems and obstacles of academic research at the Algerian University
مقال
Keywords: البحث الأكاديمي, المشاكل, المعوقات.; Academic research, problems, obstacles.